1999
DOI: 10.1016/s0254-0584(99)00078-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical-constant calculation of non-uniform thickness thin films of the Ge10As15Se75 chalcogenide glassy alloy in the sub-band-gap region (0.1–1.8eV)

Abstract: Optical-transmission spectra are very sensitive to inhomogeneities in thin ®lms. In particular, a non-uniform thickness produces a clear shrinking in the transmission spectrum at normal incidence. If this deformation is not taken into account, it may lead to serious errors in the calculated values of the refractive index and ®lm thickness. In this paper, a method ®rst applied by Swanepoel for enabling the transformation of an optical-transmission spectrum of a thin ®lm of wedge-shaped thickness into the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 27 publications
8
22
0
Order By: Relevance
“…Furthermore, the optical absorption edge can be seen clearly for all three a-Si:H samples under investigation. Our results are very similar to the results of Marquez et al [23] and have similar trend as those shown by El-Sayed and Amin [24]. Recently, Sharma and Katyal [25] have also observed similar behaviour of extinction coefficient for a-(As 2 Se 3 ) 90 Ge 10 glassy alloy.…”
Section: Determination Of the Optical Parameters Of A-si:h Thin Filmssupporting
confidence: 92%
“…Furthermore, the optical absorption edge can be seen clearly for all three a-Si:H samples under investigation. Our results are very similar to the results of Marquez et al [23] and have similar trend as those shown by El-Sayed and Amin [24]. Recently, Sharma and Katyal [25] have also observed similar behaviour of extinction coefficient for a-(As 2 Se 3 ) 90 Ge 10 glassy alloy.…”
Section: Determination Of the Optical Parameters Of A-si:h Thin Filmssupporting
confidence: 92%
“…As a whole, the obtained picture is consistent with the well-known fact that refractive index and the energy gap are inversely related to each other [11]. The oscillator energy E so is an "average" energy gap and it is approximately equals to two times of the lowest direct band gap E gd (E so ≈ 2.0 E gd ) [14][15][16][17]. In this study, the [18,19].…”
Section: Methodssupporting
confidence: 88%
“…The spectral distribution of the absorption coefficient α of the films was calculated by two procedures, the first from the relation α = 4πk/λ, depend on the values of k calculated using Swanepoel's method and the second from the formula [9], α = (1/d).ln((1 − R) 2 /T). The obtained values of α from Swanepoel's method and the well-known formula in this region are approximately in the same nearly in magnitude.…”
Section: Optical Absorption At the Fundamental Edgementioning
confidence: 99%